PERBEDAAN ANTARA PENGAJARAN METODE LANGSUNG DAN METODE TIDAK LANGSUNG TERHADAP KEMAMPUAN PASSING ATAS DALAM PERMAINAN BOLA VOLI PADA SISWA KELAS XI SMK NEGERI 1 MAKASSAR - Kurniawan, Irvan; Ismail, Agus (Jurnal Penjaskesrek, 2018)
This study aims to obtain clear information about the Difference between Teaching Direct Methods and Indirect Methods Against the Top Passing Ability in Volleyball Games in Class XI Students of SMK Negeri 1 Makassar. This study uses the experimental method with Mached by Subjects, abbreviated as the M-S pattern, which is the separation of the pairs of subjects each into the experimental group 1 and the experimental group 2 will automatically balance the two groups. Subjects In this study the sample was male students of class XI of SMK Negeri 1 Makassar with 22 students. The measurement in this study is the giving of a test (post-test) which is then given a score or number on student learning outcomes on the passing volleyball game using the direct method and indirect method. The data is then analyzed using the t test (t Test). Based on the analysis of the results of the research and discussion, it was found that there was an increase in the average ability in passing over the direct method while the passing of the indirect method obtained an average value of 29.0. indirect method.